The Role of Disruptive Technologies in Shaping Reflective Practice-Based Learning: Insights from AI and Ethical Considerations - Jensen, Camilla Gyldendahl; Dau, Susanne; Møller, Dan Eggert (Proceedings for the European Conference on Reflective Practice-based Learning 2025, 2025)
The release of OpenAI's ChatGPT in 2022 marked a new era in AI-supported education, bringing to light both the potential benefits and challenges of using AI-driven tools like chatbots in learning environments. Concerns surrounding shallow learning and potential misuse of AI have made educators cautious about integrating such tools in their teaching. This article examines how AI, particularly in academic work, can foster deeper exploration and engagement, drawing on Hannah Arendt's theories on "the human condition" to frame these insights. Using a case study that includes screenshots and transcribed dialogues from students’ interactions with ChatGPT in written assignments, this study analyzes data from approximately 100 third-year students. In response to a rapidly evolving digital landscape, the study considers the role of disruptive technologies like AI in reflective practice-based learning (RPL) and the importance of technological literacy for both education and professional practice. By situating AI within Arendt's vita activa and vita contemplativa frameworks, we explore how AI can enhance exploration and thus support RPL. Further, the article addresses ethical concerns around AI, investigating the balance between enhancing academic integrity and fostering exploration in an AI-influenced environment. Ultimately, this study contributes to discussions about the future of RPL, considering the implications of AI and other emerging technologies for educational practices. The findings aim to inform the development of pedagogical frameworks that integrate technological literacy and reflective practices, providing a foundation for understanding the ethical and practical considerations essential for future research and implementation.